Pelayanan Keperawatan, Komunikasi Terapeutik, Kepuasan Pasien Rawat Inap di RSUD dr. Loekmono Hadi Kudus - Umi Faridah; M Purnomo; Yanti Kusmiyati (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2021)
The results of the Community Satisfaction Index survey conducted at dr. LoekmonoHadi Kudus, the results of the Community Satisfaction Index survey, amounted to 78.42% below the 90% target with communication services of 58.76% which is far below the 85% target, while nursing services have a community satisfaction index of 88.7% which is still in the below the 90% target. The results of observations made on 10 nurses showed that 4 nurses had good therapeutic communication and 6 nurses had communicated therapeutically, but only daily habits or routines were not fully in accordance with the expectations of the patient. To determine the relationship between nursing services and therapeutic communication with inpatient satisfaction at dr. LoekmonoHadi Kudus. Correlational analysis using cross sectional approach. The research sample was 69 people who were taken by proportionate simple random sampling technique. The research instrument is a questionnaire that has been tested for validity and reliability. The statistical test used was the Spearman Rho. The hypothesis shows that Ha is accepted and Ho is rejected according to the results of the Spearman Rho test for nursing services obtained p value = 0.002 <Î± = 0.05 and r (Rho) = 0.613 and for therapeutic communication obtained p value = 0.000 <Î± = 0.05 and r (Rho) = 0.649. There is a relationship between nursing services and therapeutic communication with inpatient satisfaction at dr. LoekmonoHadi Kudus.